REORIENTASI PENDIDIKAN AGAMA BERBASIS MULTIKULTURALISME DAN TASAMUH - Nur hidayah (IAIN Surakarta, 2016)
This article aims to describe the growing discourse on religious education-based multicultural, then reorienting the discourse according to the concept of tasamuh. This study, with a qualitative analysis of literature, found that the instigators of the concept of multiculturalism had enough influence Muslims so that religious education should be reorientated. Reorientation does with reconciling tasamuh in religious education-based multicultural. This reorientation is important, because the mission of multicultural education containing religious pluralism, humanism, and democracy, can not be an alternative in the practice of religious education. If this model is applied in education, then this could threaten the faith and morals of students, especially for Muslim students. In society, Islam has implemented the concept of tasa>muh. With this concept, Islam made it easier for other people to not disturb the faith of Muslims. This reorientation is very appropriate for addressing diversity, with formulations that do not harm the unity of the nation, at the same time the Islamic faith was still solid.